Assessing the resilience of coral reefs against macroalgae invasion in the Sempu Island Nature Reserve, Malang District, Indonesia - ANDIK ISDIANTO; PUTRI DEVI YORARIZKA; DIAN ALIVIYANTI; SYARIFAH HIKMAH JULINDA SARI; ADI TIYA YANUAR; MUHAMMAD ARIF ASADI; ARIEF SETYANTO; GATUT BINTORO; TRI DJOKO LELONO; DINI ATIKAWATI; AULIA LANUDIA FATHAH; BERLANIA MAHARDIKA PUTRI; SUPRIYADI SUPRIYADI; OKTIYAS MUZAKY LUTHFI (Society for Indonesian Biodiversity, 2024)
Abstract. Isdianto A, Yorarizka PD, Aliviyanti D, Sari SHJ, Yanuar AT, Asadi MA, Setyanto A, Bintoro G, Lelono TD, Atikawati D, Fathah AL, Putri BM, Supriyadi, Luthfi OM. 2024. Assessing the resilience of coral reefs against macroalgae invasion in the Sempu Island Nature Reserve, Malang District, Indonesia. Biodiversitas 25: 2877-2887. The living coral cover in the Sempu Strait is known to be stuck in the range of 37% due to average data from 2009-2016. Several coral diseases have been documented in this region, which can result in the transformation of coral reefs into algae-dominated communities. This study examines the dynamic interplay between coral reefs and macroalgae within the marine ecosystems of the Sempu Island Nature Reserve, Malang District, Indonesia. Conducted across five research stations, our analysis utilized the Underwater Photo Transect (UPT) method, combined with image analysis tools CPCe and Image-J, and statistical analysis through SPSS. The findings indicate a persistent competition between corals and macroalgae, exacerbated by sedimentation from port activities and river discharges, and significant nutrient loads from human settlements. The average living coral coverage varied significantly, with a range from 12% to 53% across the study period, while macroalgae coverage showed an increase, especially in turf algae. The correlation analysis revealed a 'quite strong' relationship (r=0.783 between coral and macroalgae coverage, suggesting that increases in coral cover could potentially facilitate macroalgae proliferation under current environmental conditions. Notably, the study highlighted the critical role of water quality parameters such as temperature, pH, and salinity, which were within optimal ranges yet facilitated competitive interactions. This research underscores the complexity of coral-macroalgae relationships and the pressing need for integrated management strategies focusing on water quality and habitat preservation to ensure the resilience of these critical marine ecosystems.